PENGARUH PEROLEHAN BONUS SWBI DAN IMBALAN PUAS TERHADAP PEMBIAYAAN PERBANKAN SYARIAH - Saptohadi, Totok (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
Problems which are encountered by Shariah Banking is the difficulties in controlling its liquidity efficiently, considering the opportunity to invest immediately the received saving funds as well as the difficulties in liquidifying the in progress investment funds when there is withdrawal in critical situation, so the Shariah banking withhold its liquidify instrument in a bigger amount than the conventional banking. This matter causes the average income of syariah banking reducing. The purpose of this research is to analyze some factors which influence bonus acquisition at SWBI and reward at PUAS to the shariah banking financing. Reporting research is applied as method in which the researcher obtains the secondary data from Bank Indonesia in the form of monthly data and annual data of Shariah Commercial Bank and Shariah Business Unit from all over Indonesia which is packed in the form of statistic in 2006-2010 periods. The result of hypothesis test states that simultaneously the SWBI and PUAS variables have significant influence to the financing level while partially the SWBI variable has significant influence, while the PUAS variable has no significant influence to the financing level.Keywords: Wadiah Certificate of Bank Indonesia, ShariahInterbank Money Market, Shariah Banking Financing